Dissolution Study of Biodegradable Magnesium Silicide Thin Films for Transient Electronic Applications - Gu, Ji-Woo; Shim, Jun-Seok; Chae, Minjung; Jung, Yoonseong; Kim, Su-Min; Ryu, Young-In; Lee, Jae-Hwan; Kim, Sung-Woo; Kim, Kyung-Sub; Lee, Tae-Woo; Wyszkowska, Edyta; Shin, Jungho; et al. (Wiley-VCH Verlag, 2026)
Transient electronic systems offer compelling solutions for sustainable technologies, enabling environmentally benign disposal in ecological settings and eliminating surgical retrieval in biomedical implants. At the core of such systems, biodegradable semiconductors serve as key materials not only for logic operations but also for realizing diverse sensing modalities. Here, a comprehensive study of magnesium silicide (Mg2Si) thin films as a narrow-bandgap, biodegradable semiconductor platform for transient electronics is reported. Polycrystalline Mg2Si thin films are formed via RF magnetron sputtering and thermal annealing, followed by systematic investigation of their dissolution behavior under various pH and ionic conditions. Physiological relevance is confirmed by phosphate-buffered saline testing, while environmental biodegradability is validated under composting conditions. In vitro cytotoxicity assays confirmed the biocompatibility of the material and its degradation byproducts. Mg2Si thin films exhibit an indirect bandgap of ≈0.84 eV, intrinsic carrier concentration (>1018 cm−3), and thermal conductivity (<1.8 W m−1 K−1), along with broadband optical absorbance. Device-level integration into thermoelectric harvesters yielded Seebeck coefficients of ≈130 µV K−1 and output power exceeding ≈0.338 µW cm−2 K−2. Photosensors demonstrated photoresponse up to 1300 nm, confirming near-infrared sensitivity. These results establish Mg2Si as a viable semiconductor for transient electronics, expanding the material spectrum beyond conventional wide-bandgap semiconductors.